Association of smoked cannabis with treatment resistance in schizophrenia. (August 2019) - Arsalan, Arsalan; Iqbal, Zafar; Tariq, Muhammad; Ayonrinde, Oyedeji; Vincent, John B.; Ayub, Muhammad
Highlights: This study examines the association between smoking cannabis and treatment resistance to schizophrenia. There is an association between the cannabis use and lack of response to antipsychotic treatment. We selected our sample from a tertiary care hospital and overall rate of treatment resistance was 60%. Abstract: Association of cannabis use with schizophrenia is a well-established finding. Its role in causation, however, is debated. Different studies have found that cannabis use impacts the outcome of schizophrenia and is associated with treatment non-adherence and a higher rate of relapses. In this paper, we investigated the impact of self-reported cannabis use on treatment response in a cohort of schizophrenia patients from Pakistan, a middle-income country. The data was collected from a psychiatric hospital in Khyber Pakhtunkhwa province of Pakistan where cannabis use is prevalent. Clinical evaluation and therapeutic response were established using the Positive and Negative Syndrome Scale (PANSS), and Clinical Global Impressions Scales-Severity (CGI-S) and Improvement (CGI-I) scale. Lack of response to adequate treatment with two trials of antipsychotics was classed as treatment resistance. We compared the treatment-resistant and treatment responsive groups for different variables including cannabis use, age at onset of illness, duration of untreated psychosis and consanguinity. We had data on 230 patients. More than ninety percent of our participants were men. The rate of treatment resistance was over 60%. Ongoing use of cannabis had an association with treatment resistance. We only included cases where treatment adherence was not a problem.